Dois casos de Quérion por Trichophyton mentagrophytes - Silva, AV (2012)
Introduction: Kerion celsi is the rare and inﬂ ammatory form of tinea capitis which is caused by dermatophyte fungi. Diagnosis is not easy due to the delay in cultural examination and the need to consider various etiologies in the differential diagnosis. Treatment must be prolonged and requires systemic antifungals. Since griseofulvin was discontinued in the Portuguese market, it has been necessary to consider therapeutic alternatives.